Factors affecting food security status of households in the rural coastal community of Barangay Talisay, Hinatuan, Surigao del Sur - Pandan, Carth Glouie A.; Hualda, Luis Antonio T. (Davao City School of Management, University of the Philippines Mindanao, 2016)
This study aims to measure the food security level of households in the rural coastal community of Barangay Talisay, Hinatuan, Surigao del Sur. Factors affecting their food security status and coping strategies they adopted were also identified. Household Food insecurity Access Scale (HFIAS) was used to measure the prevalence of household food insecurity in the barangay. Household Food Insecurity Access Prevalence (HFIAP) was used to categorize the rural coastal households according to their food security level. A total of 167 households were surveyed for this study. A multiple linear regression model was estimated based on this data with the HFIAS scores of each household as the dependent variable and a set of socio-demographic characteristics variables including the twelve coping strategies of the Coping Strategies Index (CSI) as explanatory variables. Coping Strategies Index (CSI) was used to determine the frequent survival coping strategies adopted and practiced by households in the rural coastal barangay in times of food shortage and lack of money to buy food. It was found that50 percent of the surveyed households are severely food insecure, 36 percent are moderately food insecure, 10 percent are mildly food insecure and only 4 percent are food secure. Results of the regression analysis showed that household income, household size and main occupation as fisherman are the main factors that affect food security. The coping strategies frequently adopted by households in the area are relying on less preferred and less expensive foods, borrowing foods, purchasing food on credit, eating immature crops, consuming seed stocks, limiting portion size and reducing number of meals eaten in a day. Presence of sari-sari stores and itinerant vendors showed an important relationship on food security of the households in the barangay in terms of providing available supply of food all the time. This study makes a contribution to the understanding of the basic food security aspects and factors affecting households? food security in Barangay Talisay and may act as reference source for improving the food security status of households in the area.
Thesis (BS Agribusiness Economics)-- University of the Philippines Mindanao, June 2016